Lack of an association between marital status and survival in patients receiving stereotactic body radiotherapy for early-stage non-small-cell lung cancer. - Noriko Kishi; Yukinori Matsuo; Hideki Hanazawa; Yusuke Iizuka; Takashi Mizowaki (PLoS ONE, 2022)
Marital status has been proposed as a promising prognostic factor in many malignancies, including non-small-cell lung cancer (NSCLC). However, its prognostic value is still unclear for individual non-surgical treatments for stage I NSCLC. This study investigated the prognostic value of marital status in patients with early-stage NSCLC treated with stereotactic body radiotherapy (SBRT). Patients with early-stage NSCLC treated with SBRT between January 2003 and March 2014 at our institute were enrolled, and marital status at the time of SBRT was investigated. Propensity score matching (PSM) was applied to reduce potential selection bias between the married and unmarried groups. Two hundred and forty patients (median age 77 years; 152 married, 87 unmarried) were analyzed. The unmarried included higher proportions of the elderly, women, never smokers, and those with decreased pulmonary function compared to the married. PSM identified 53 matched pairs of married and unmarried patients, with no significant difference in patient background parameters. The 5-year overall survival (OS) was 52.8% and 46.9% in the married and unmarried groups, respectively (P = 0.26). There was no significant difference in NSCLC death or non-NSCLC death between the two groups (P = 0.88 and 0.30, respectively). There was no significant difference in OS between married and unmarried male patients (n = 85, 5-year OS, 52.6% vs. 46.0%; P = 0.42) and between married and unmarried female patients (n = 21, 54.5% vs. 50.0%; P = 0.44). In conclusion, marital status was not associated with OS in patients receiving SBRT for early-stage NSCLC.